The Impact of Sports Tourism Motivation on Tourist Loyalty: The Chain Mediation Effect of Experience Quality and Tourist Satisfaction - Wantara, Pribanus; Irawati, S. Anugrahini; Arfy, Widya Rizka; Purwanto, Hery (Journal of Posthumanism, 2026)
This study aims to analyze the structural relationship between sports tourism motivation, experience quality, tourist satisfaction, and tourist loyalty in the context of international sports tourism, using empirical evidence from the 2025 Mandalika MotoGP in Indonesia. This study also explores the mediating role of experience quality and satisfaction in the relationship between motivation and tourist loyalty. A quantitative approach was used through Structural Equation Modeling (SEM) based on data from 300 respondents from ten countries. The research instrument was developed from validated constructs in the literature on sports tourism and service quality. Data analysis was conducted using SmartPLS 4.0 to test the measurement and structural models. The results indicate that all tested relationships are positive and statistically significant. Sports tourism motivation has a strong influence on experience quality, as well as direct and indirect influences on tourist loyalty through experience quality and tourist satisfaction. The R² values ​​for experience quality (0.617) and tourist loyalty (0.672) demonstrate the model’s strong ability to explain variance in sports tourism behavior.